2019
DOI: 10.1002/ajmg.a.61301
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype evolution and health issues of adults with Beckwith‐Wiedemann syndrome

Abstract: Background: Beckwith-Wiedemann syndrome (BWS) phenotype usually mitigates with age and data on adulthood are limited. Our study aims at reporting phenotype evolution and health issues in adulthood.Methods: 34 patients (16 males), aged 18-58 years (mean 28.5) with BWS were enrolled.Results: 26 patients were molecularly confirmed, 5 tested negative, and 3 were not tested. Final tall stature was present in 44%. Four patients developed Wilms' Tumor (2, 3, 5, and 10 years, respectively); one hepatoblastoma (22 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
5
21
0
Order By: Relevance
“…Notably, new evidence does support an increase in cancer risk for BWSp beyond childhood. 25 (3) We did not have access to patient medical records, and thus could not determine each subject’s age or date at clinical syndrome diagnosis in case this age differed from the molecular diagnosis. It is likely that, in some instances, the BWSp diagnosis was prompted by the development of a childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, new evidence does support an increase in cancer risk for BWSp beyond childhood. 25 (3) We did not have access to patient medical records, and thus could not determine each subject’s age or date at clinical syndrome diagnosis in case this age differed from the molecular diagnosis. It is likely that, in some instances, the BWSp diagnosis was prompted by the development of a childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that during this early period the face was round to oval with prominent cheeks, and emphasized that the typical facial appearance improved as the age got older. However, Gazzin, et al (2019) evaluated adult BWS patients, and showed prognathism in their photographs. In the patients presented here with classical phenotype, while coarse face with prominent cheeks and micrognathia were noticeable in IC1 subgroup, IC2 subgroup showed a round face, prominent cheeks, micrognathia, severe macroglossia, facial naevus simplex, and ear creases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Overall, the oncologic risk is highest for patients with BWS in the first two years of life, [ 1 ] and after ten years of age, the tumor risk approaches that of the general population. [ 6 ] There is no evidence of an increased risk of malignant tumors in adults with BWS, [ 1 ] although hepatoblastoma, acute lymphoblastic leukemia, adrenal adenoma, testicular Sertoli cell tumor, and three benign tumors (hepatic hemangioma, uterine myoma, and mammary fibroepithelioma) have been reported in young adults with BWS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%